1974
DOI: 10.1083/jcb.61.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Action of Cytochalasin D on Cells of Established Lines

Abstract: HeLa, Vero, L, HEp2, and MDBK cells respond immediately to 0.2–0.5 µg/ml cytochalasin D (CD) with sustained contraction (contracture), loss of microvilli, expression of endoplasmic contents (zeiosis), nuclear protrusion, and extension of cytoplasmic processes. The development of these changes is depicted, and the dose-response patterns in these cell lines are described. MDBK is generally most resistant and HeLa most sensitive to these effects of CD. Cells in G1 are most sensitive to CD; responsiveness decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(135 citation statements)
references
References 115 publications
9
126
0
Order By: Relevance
“…2 d). As has been shown in other SEM studies (Miranda et al, 1974), cytochalasin B was found to cause HeLa cells to contract, lose microvilli and develop blunt, knobby projections. Such cells were unable to mediate redistribution of virus particles across their surface (Fig.…”
Section: Scanning Electron Microscopymentioning
confidence: 52%
“…2 d). As has been shown in other SEM studies (Miranda et al, 1974), cytochalasin B was found to cause HeLa cells to contract, lose microvilli and develop blunt, knobby projections. Such cells were unable to mediate redistribution of virus particles across their surface (Fig.…”
Section: Scanning Electron Microscopymentioning
confidence: 52%
“…As a control for possible CB effects caused by alteration of hexose transport, experiments were performed using cytochalasin D (18,31,36). Results similar to those described above were obtained with cytochalasin D; however, recovery from cytochalasin D was a slower process.…”
Section: E (Arrows)mentioning
confidence: 98%
“…One of the effects of cytochalasins on living cells which is not observed with pure actin in vitro is a rearrangement of the actin-containing components of their cytoskeletons into aggregated masses (references 20, 21, 35, and 52, among others; review in reference 18). This rearrangement is dependent on metabolic energy (20,21,34,43) and is accompanied by little or no depolymerization of cellular actin (3, 36). We have previously reported that treatment of HEp-2 cells with cytochalasin D (CD) induced an increase in the relative content of total cellular actin (36).…”
mentioning
confidence: 99%